A new paradigm for high‐dimensional data: Distance‐based semiparametric feature aggregation framework via between‐subject attributes - Liu, Jinyuan; Zhang, Xinlian; Lin, Tuo; Chen, Ruohui; Zhong, Yuan; Chen, Tian; Wu, Tsungchin; Liu, Chenyu; Huang, Anna; Nguyen, Tanya T.; Lee, Ellen E.; Jeste, Dilip V.; et al. (Scandinavian journal of statistics, 2024)
This article proposes a distance‐based framework incentivized by the paradigm shift toward feature aggregation for high‐dimensional data, which does not rely on the sparse‐feature assumption or the permutation‐based inference. Focusing on distance‐based outcomes that preserve information without truncating any features, a class of semiparametric regression has been developed, which encapsulates multiple sources of high‐dimensional variables using pairwise outcomes of between‐subject attributes. Further, we propose a strategy to address the interlocking correlations among pairs via the U‐statistics‐based estimating equations (UGEE), which correspond to their unique efficient influence function (EIF). Hence, the resulting semiparametric estimators are robust to distributional misspecification while enjoying root‐n consistency and asymptotic optimality to facilitate inference. In essence, the proposed approach not only circumvents information loss due to feature selection but also improves the model's interpretability and computational feasibility. Simulation studies and applications to the human microbiome and wearables data are provided, where the feature dimensions are tens of thousands.